Anthropolinguistic Approach to Pantun Melayu Deli from the Lebah Begantong Music Group - Tarigan, Mita Ariani Br; Dardanila, Dardanila; Kudadiri, Amhar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is a qualitative descriptive study which aims to determine the cultural meaning and analysis of the anthropolinguistic approach to Malay pantun from the Lebah Begantong music group. The Lebah Begantong music group is a local music group originating from North Sumatra. The Lebah Begantong music group not only performs traditional Malay songs, but also witty rhymes that invite fun, laughter and humor. From the results of the research found, the meaning contained in Malay pantun chants consists of four meanings, namely the meaning of happy expressions, the meaning of advice, the meaning of satire and the meaning of entertainment. Three analytical ideas were found in the anthropolinguistic approach, namely performance, indexicality and participation. The concept of performance which consists of text analysis, co-text and context, the concept of indexicality which consists of indices, signs and symbols and the concept of participation, namely the response and involvement of the audience.